Office-based ocular procedures for the allergist. Issue 5 (October 2019) - Leonardi, Andrea; Borghesan, Franco; Scalora, Tania; Modugno, Rocco Luigi; Bonaldo, Alex
Abstract : Purpose of review: The aim of this study is to suggest principles for ocular procedures to be performed by allergists in their offices in helping their diagnosis of ocular diseases and suggest better interactions between allergists and ophthalmologists. Recent findings: Diagnosis of ocular allergy is based on clinical history and signs and symptoms, with the support of in-vivo and in-vitro tests for the identification of the specific allergen. Unfortunately, ocular manifestations are frequently misdiagnosed and not properly managed. Summary: A multidisciplinary allergist–ophthalmologist approach may improve early differential diagnosis and the prognosis of patients with allergic disease and conjunctivitis through shared management and earlier etiological treatment.